2006
DOI: 10.22163/fteval.2006.166
|View full text |Cite
|
Sign up to set email alerts
|

What Can Be Achieved By Special R&D Funds When There is No Special Leaning Towards R&D Intensive Industries?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…In addition, the effect of direct public financial support for business R&D is generally positive (although modest), but intellectual property rights increase patenting while having little impact on R&D spending. Similarly, Falk and Leo (2006) find that although public R&D funding has positive effects, the dynamics of GDP growth and R&D prone industry structure (measured by the share in value added) seem to be more important drivers behind the business sector's R&D efficiency. By considering the efficiency of different specialized sub-processes (capital, labour technological balance of payment, article-oriented and patenting) in the NIS, Lee and Park (2005) have found that most Eastern European countries show low output efficiency in most sub-processes, with only Hungary showing a high efficiency in production of academic papers.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the effect of direct public financial support for business R&D is generally positive (although modest), but intellectual property rights increase patenting while having little impact on R&D spending. Similarly, Falk and Leo (2006) find that although public R&D funding has positive effects, the dynamics of GDP growth and R&D prone industry structure (measured by the share in value added) seem to be more important drivers behind the business sector's R&D efficiency. By considering the efficiency of different specialized sub-processes (capital, labour technological balance of payment, article-oriented and patenting) in the NIS, Lee and Park (2005) have found that most Eastern European countries show low output efficiency in most sub-processes, with only Hungary showing a high efficiency in production of academic papers.…”
Section: Introductionmentioning
confidence: 91%
“…The cross-country study by Guellec and van Pottelsberghe (2003) suggests a complementarity between public funds to support R&D in the private sector. Furthermore, R&D expenditure performed in the public sector, in particular in the defence sector, appears to crowd out private R&D. Building up on this model, Falk and Leo (2006) investigate the effects of different public support channels on the R&D spending in the business sector of 15 Western European countries, putting a focus on the case of Austria. Contrary to Guellec and van Pottelsberghe (2003), they use four-year averages instead of annual data and estimate their approach by using the fixed effects method and the generalized method of moments (GMM) estimator.…”
Section: Efficiency Of Randd Policiesmentioning
confidence: 99%
“…Once real damage is identified, we employ a method to estimate the number of pixel grids, enabling quick and convenient determination of the area for each damage point. In scenarios with limited samples, the advanced U-Net++ algorithm [26][27][28], based on the U-shaped architecture of fully convolutional networks, is selected. It can capture features at various levels and integrate them through feature concatenation, resulting in higher accuracy in image segmentation.…”
Section: 2algorithm and Model Trainingmentioning
confidence: 99%